Intranasal cerium oxide nanoparticles improves locomotor activity and reduces oxidative stress and neuroinflammation in haloperidol-induced parkinsonism in rats - Mohammad,; Khan, Urooj Ahmed; Warsi, Musarrat Husain; Alkreathy, Huda Mohammed; Karim, Shahid; Jain, Gaurav Kumar; Ali, Asgar (Frontiers in Pharmacology, 2023)
Introduction: Cerium oxide (CONPs) nanoparticles have been investigated for their therapeutic potential in Parkinson’s disease (PD) due to their potent antioxidant activity. CONPs have ability between cerium’s +3 and +4 oxidation states and act as regenerative free radical scavenger due to oxygen defects in their lattice structure. Method: The penetration of the synthesized CONPs was evaluated using confocal microscopy in the goat nasal mucus layers. Nasal cilio toxicity study was done to understand the biocompatibility of prepared CONPs. Antioxidant activity was evaluated using FRAP assay method. For in vivo study, total 16 rats were divided into four groups namely group 1: Negative control, group 2: haloperidol-induced control, group 3: haloperidol-induced treated with levodopa, and group 4: haloperidol-induced treated with CONPs. Open field test and Pole test were performed for neurobehavioral evaluation of the prepared CONPs. Gamma scintigraphy study was done to understand the deposition of CONPs in the brain following intranasal administration. The neuroprotective effect of the prepared CONPs was assessed via histopathological study. Finally, the effect of CONPs on oxidative stress was assessed in brain via biochemical estimations. Results: Confocal microscopy showed deep and homogenous distribution of CONPs in the goat nasal mucus layers. No signs of irritation were seen in nasal membrane when treated with CONPs. The FRAP assay revealed highest antioxidant activity of prepared CONPs at a concentration of 25 µg/mL. In-vivo motor manifestation studies showed highly significant (p <0.001) improvement in cognitive impairment when rats treated with intranasal CONPs as compared to untreated group. Histopathological studies showed reduction in neurodegeneration in the treatment group. The amount of thiobarbituric acid reactive substances (TBARS) was reduced significantly, whereas the levels of catalase (CAT), superoxide dismutase (SOD), and GSH were increased significantly, while amounts of interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α) showed significant reduction after intranasal administration of CONPs. High dopamine concentration (13.93 ± 0.85 ng/mg protein) was observed as compared to haloperidol-induced control rats (5.76 ± 0.70 ng/mg protein). Conclusion: The overall results indicate that the prepared CONPs have found to be useful in ameliorating oxidative stress and able to efficiently manage the Parkinson disease.